(untitled) (Global Journal of Human-Social Science, 2012)
This paper provides an overview of the dynamics of religion political godfatherism i e the act of mentoring people into political office for purposes of indirect control of appointments and public funds and democratization in the South Eastern Nigeria with a special focus on Anambra state since 1999 when the country returned to civilian rule after sixteen years of military rule Methodologically this paper adopted public choice theory and survey methods of inquiry with 1800 questionnaires distributed With the aid of tables and arithmetic percentage formula this paper observes that political elites hijacked party structures using party financing and impose candidates after reaching agreements with them on the party and the state for purposes of rent seeking and political dominance Religious oaths using African Traditional Religious rituals were used to safeguard these pre-electoral agreements and by the application of existing political schisms between Catholic and Anglican churches they seek support for their candidates Tussle for political power between these two churches and between them and individual godfathers which ended in the triumph of institutional godfathers followed This opened sources of resources for churches through the appointment of their members into political positions This paper therefore concludes that religious belief and affiliation fundamentally decide electoral choice and political appointments in Anambra state